Intramolecular Phl=O mediated copper-catalyzed aziridination of unsaturated sulfamates: A new direct access to polysubstituted amines from simple homoallylic alcohols - Duran, Fernando Javier (2002)
(Matrix presented) Olefinic sulfamates derived from primary and secondary alcohols undergo intramolecular copper-catalyzed aziridination in the presence of iodosylbenzene to afford novel bicyclic fused aziridines. The latter were opened by various nucleophiles to give the corresponding substituted cyclic sulfamates, which in turn reacted, after nitrogen activation, with a second nucleophile at the carbon atom bearing the oxygen atom. Concomitant removal of the sulfonyloxy moiety thus gave access to polysubstituted amines.